Hubungan Struktur Kepemilikan, Komite Audit dan Biaya Research and Development terhadap Intellectual Capital Disclosure - Muhammad Ryu Syaputra; Afrizal, Afrizal; Fredy Olimsar (Dharma Ekonomi, 2025)
This study aims to analyze the relationship between managerial ownership, institutional ownership, audit committee, and research and development (R&D) expenses on Intellectual Capital Disclosure (ICD) in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Intellectual Capital Disclosure is essential as it reflects a company’s ability to manage knowledge, innovation, and human resources that serve as its competitive advantage. This research employs a quantitative approach using the total sampling method, where all healthcare sector companies that meet the criteria are included as samples. Secondary data were obtained from annual reports and analyzed using panel data regression with the assistance of Stata 19 software. Model selection was conducted through Chow, Hausman, and Lagrange Multiplier (LM) tests, with the results indicating that the Random Effect Model (REM) was the most appropriate model to use. The results show that managerial ownership, institutional ownership, and audit committee have negative and insignificant relationships with Intellectual Capital Disclosure. In contrast, research and development activities have a positive and significant relationship with Intellectual Capital Disclosure.